Politics of appearances: Some reasons why the UN‐REDD project in Central Sulawesi failed to unite the various stakeholders. (April 2015) - Howell, Signe
Abstract REDD+ (Reducing Emissions from Deforestation and Forest Degradation) started as a global project aimed at reducing CO2 emissions by protecting tropical forests. At the same time, several so‐called co‐benefits were listed in the original documents, such as biodiversity and other environmental services, poverty reduction and sustainable livelihoods, and good governance. I argue that REDD+ quickly became a project in which these co‐benefits have emerged to be of central concern and that the rights of affected forest populations today dominate much of the REDD+ discourse. One reason for the redirected focus of REDD+ can be attributed to the activities of international and national environmental and human rights organisations. While this has arguably contributed to a process of democratisation in Indonesia, it has also slowed down the implementation of readiness projects. Taking my example from the UN‐REDD initiative in Central Sulawesi, I examine some reasons why it has been difficult to establish the proposed five REDD sites in the province.